MAKNA UANG BAGI MAHASISWA DALAM PERSPEKTIF SOSIOLOGI - Purba, Ranada; Marnelly, Tengku Romi; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to determine the meaning of money and its social implications for students who are bidikmisi scholarship recipients and single tuition payers V FISIP UNRI. This study uses a qualitative research method with a phenomenological approach. Data collection was carried out using in-depth interviews, observation, and documentation techniques. The subjects in this study were six students of the Bidikmisi scholarship and single tuition fee payers (STF) V FISIP UNRI using a purposive sampling technique based on certain criteria. The results of this research show that money is very important. Almost all aspects of human life are related to money. because the different socio-economic conditions in each student lead to different meanings in interpreting money. For students receiving Bidikimisi: Money is something valuable and valuable, Money as a fulfillment of basic needs, No money will have an impact on psychological and inner peace, Money as a form of gratitude, Money as a symbol of equality or not. For Students Paying Single Tuition Fees (STF) V: The meaning of money as a measure of behavior and attitudes, as a tool to achieve something in the future, as a creator of happiness by helping others, and upholding the value of simplicity. Likewise with the implications of the meaning of money which is something that is produced or as a consequence of the implementation of the meaning of money. For bidikmisi students, the meaning of money implies that they have to work hard to earn money to meet basic needs. while for students who pay single tuition payers (STF) V the implication of the meaning of money being present is freedom, appreciation, and social recognition as well as a point of self-actualization.